Click Assembly of Dye-Functionalized Octasilsesquioxanes for Highly Efficient and Photostable Photonic Systems - Perez-Ojeda Rodriguez, Maria Eugenia; Trastoy Bello, Beatriz; Lopez-Arbeloa, Iñigo; Bañuelos, Jorge; Costela, Angel; García-Moreno, Inmaculada; Chiara, Jose Luis (Chemistry - A European Journal, 2011)
New hybrid organicinorganic dyes based on an azide-functionalized cubic octasilsesquioxane (POSS) as the inorganic part and a 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BDP) chromophore as the organic component have been synthesized by copper(I)-catalyzed 1,3-dipolar cycloaddition of azides to alkynes. We have studied the effects of the linkage group of BDP to the POSS unit and the degree of functionalization of this inorganic core on the ensuing optical properties by comparison with model dyes. The high fluorescence of the BDP dye is preserved in spite of the linked chain at its meso position, even after attaching one BDP moiety to the POSS core. The laser action of the new dyes has been analyzed under transversal pumping at 532 nm in both the liquid phase and when incorporated into solid polymeric matrices. The monosubstituted new hybrid dye exhibits high lasing efficiency of up to 56% with high photostability, with its laser output remaining at the initial value after 4x10(5) pump pulses in the same position of the sample at a repetition rate of 30 Hz. However, functionalization of the POSS core with eight fluorophores leads to dye aggregation, as quantum mechanical simulation has revealed, worsening the optical properties and extinguishing the laser action. The new hybrid systems based on dye-linked POSS nanoparticles open up the possibility of using these new photonic materials as alternative sources for optoelectronic devices, competing with dendronized or grafted polymers.
Keywords: azides; click chemistry; dyes; pigments; hybrids; silsesquioxanes